the Speech Acts of the Lecturers in Teaching English - Nilma Taula'bi' (UKI TORAJA, 2015)
This research aims are to find out the types and the functions of speech acts those are used by the lectures in teaching English and to describe the students’ perception toward the use of speech acts by the lecturers in lecturing process. This research employed qualitative method. The subjects of this research were the lecturers and the students at English Education Study Program of FKIP UKI Toraja. The result of the research revealed that (1) the types of speech acts used by the lecturers in teaching English at English Education Study Program of FKIP UKI Toraja are assertives (assertive, affirmative and informative), directives (asking question, suggest, command and request), commisives (offer and promise), declaratives (declare) and expressives (feeling expression, greeting, parting, thanking, and praising) and those are expressed directly and indirectly, (2) the functions of the speech acts used by the lecturers in teaching English at English Education Study Program of FKIP UKI Toraja are statement, asking question, command and request, (3) the students prefer the lecturers expressed their utterances directly because it is easy for them to grasp the meaning of the utterances and respond the lecturers’ utterances. The students also prefer the lecturers mixtheir language and using body language or gesture to convey the materials in the lecturing process. The students were responded the lecturers’ utterance in verbal, nonverbal and both of them. According to the students, the lecturers’ utterances can help the students to improve their language competence, as a motivation for the students, can increase their vocabulary to implement in their communication, help them to imitate and practice the way in pronouncethe words correctly.